High-performance dry powder mixed asphalt mixture and preparation method thereof

By using high-performance dry powder mixing technology in asphalt mixture, fractal fibers are prepared and combined with composite fiber materials, the problem of performance deterioration of asphalt mixture under complex environmental conditions is solved, the high-temperature stability and low-temperature crack resistance are significantly improved, and the service life of the road surface is extended.

CN119859035AActive Publication Date: 2025-04-22DALIAN DINGLI CONSTRUCTION MUNICIPAL ENGINEERING MATERIALS MANAGEMENT CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510355155.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-22
Estimated Expiration
2045-03-25

AI Technical Summary

Technical Problem

Under complex environmental conditions, the performance of asphalt mixture is susceptible to freeze-thaw cycles, resulting in performance deterioration and cracking diseases, affecting the safety and service life of the road.

Method used

The preparation method of high-performance dry powder mixed asphalt mixture is adopted to prepare the precursor A by mixing polyacrylonitrile, metal oxide and solvent, and the precursor B is prepared by combining cyclodextrin, calcium chloride and other components. The fractal fiber is obtained by conjugated electrospinning with high-voltage electric field, and then cut into composite fiber material after impregnation treatment, and dry mixing is combined with aggregate, fly ash and asphalt, and finally ore powder is added.

Benefits of technology

This method makes the composite fiber material more evenly dispersed in the mixture, enhances the adhesion and internal friction, significantly improves the high-temperature stability and low-temperature crack resistance of the mixture, and extends the service life of the road surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859035A_ABST
    Figure CN119859035A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of asphalt mixtures, and particularly discloses a high-performance dry powder mixed asphalt mixture and a preparation method thereof. The invention relates to a preparation method of a high-performance dry powder blended asphalt mixture, which comprises the following steps: 1) uniformly mixing polyacrylonitrile, a metal oxide and a solvent to prepare a precursor solution A; 2) dissolving cyclodextrin in absolute ethyl alcohol to prepare a base solution; then adding calcium chloride, lauryl polymethacrylate, polycaprolactone and a surfactant, and uniformly mixing to prepare a precursor solution B; 3) performing conjugate electrostatic spinning on the precursor solution A and the precursor solution B to obtain fractal fibers; the high-performance dry powder mixed asphalt mixture is prepared by the following steps of (1) preparing an impregnation liquid, (2) preparing a fractal fiber material, (3) preparing an impregnation liquid, (4) performing impregnation treatment on fractal fibers in the impregnation liquid to obtain a composite fiber material, and (5) taking aggregate, fly ash and the composite fiber material for dry mixing, then adding asphalt for continuous mixing, and then adding mineral powder for uniform mixing to obtain the high-performance dry powder mixed asphalt mixture which has the advantages of high stability and cracking resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of asphalt mixtures, and more specifically, to a high-performance dry powder asphalt mixture and a preparation method thereof. Background Art

[0002] Asphalt mixture is widely used as the upper layer material of road structure because of its excellent road performance. However, in complex environmental conditions such as seasonal frozen soil areas, the upper layer structure will be directly affected by the freeze-thaw cycle, resulting in performance degradation and cracking, which will have an adverse impact on road driving safety and the service life of the road surface, and also increase the operation and maintenance costs of the road.

[0003] In order to improve the service status of the pavement, adding fibers to asphalt mixtures has been proven to be an effective way to improve the durability of the pavement and extend its service life, and to a certain extent meet the service requirements of pavement materials under complex environmental conditions. Asphalt mixtures are typical multiphase composite materials, and the material system is complex, multi-level and variable. Especially after adding fibers, in addition to the asphalt mortar / aggregate interface, a large number of new asphalt mortar / fiber interfaces are formed in the system, which not only changes the performance of the asphalt mortar, but also affects the bonding state of the asphalt mortar / aggregate interface, and finally forms multiple interfaces of asphalt mortar / fiber / aggregate. This multiple and complex interface behavior greatly affects the mechanical response of the asphalt mixture, and then affects the crack resistance, durability and service life of the pavement.

[0004] At present, the fiber types used at home and abroad mainly include plant fiber, polymer fiber, mineral fiber and inorganic fiber. For example, adding basalt fiber can increase the viscosity of asphalt mortar, inhibit asphalt flow, and enhance the mechanical properties of asphalt mortar. Adding polyacrylonitrile fiber can significantly improve the anti-rutting performance of asphalt mixture, but polyacrylonitrile fiber has high requirements for construction temperature. Glass fiber can improve the anti-cracking performance and high temperature performance of asphalt mixture, but glass fiber is brittle and difficult to produce and construct.

[0005] In response to this, technicians have developed a composite fiber process. For example, the patent application with application publication number CN106431088A discloses a method for preparing a fiber cold patch asphalt mixture, in which polyester fiber, lignin fiber, etc. are added to the asphalt mixture, which improves the road performance of the asphalt mixture to a certain extent, including Marshall stability, high temperature stability, low temperature crack resistance, and water stability. Another example is the patent application document with application publication number CN103739239A discloses a composite fiber material for asphalt mixture, which is formed by mixing three different types of fiber materials, lignin fiber, basalt fiber, and sepiolite fiber, in proportion. It can extend the improvement effect of single fiber material on the road performance of asphalt mixture to the composite fiber material, and the composite fiber material can comprehensively improve the various road performances of the road asphalt surface layer.

[0006] For the composite fibers in the above documents, although the corresponding performance can be improved to a certain extent through the complementary effect of different fibers, with the introduction of multiple fibers, the mechanical properties of each fiber, such as fracture strength, elastic modulus and other indicators, vary greatly, which will introduce more types of asphalt mortar / fiber interfaces into the system, affecting the mechanical response of the fiber asphalt mixture, and further affecting the comprehensive performance of the pavement, such as anti-cracking. Summary of the invention

[0007] In order to further improve the comprehensive performance of fiber-doped asphalt mixture, the present application provides a high-performance dry powder mixed asphalt mixture and a preparation method thereof.

[0008] In the first aspect, the present application provides a method for preparing a high-performance dry powder asphalt mixture, which adopts the following technical solution: A method for preparing a high-performance dry powder asphalt mixture comprises the following steps: 1) Mix polyacrylonitrile, metal oxide and solvent and stir them to obtain a precursor solution A; 2) Dissolve cyclodextrin in anhydrous ethanol to prepare a base solution; then add calcium chloride, polylauryl methacrylate, polycaprolactone, and a surfactant and mix evenly; then introduce excess carbon dioxide, let stand, and degas to obtain a precursor solution B; 3) Precursor solution A and precursor solution B are respectively delivered into syringes, and conjugate electrospinning is performed under the action of a high voltage electric field, and fractal fibers are obtained after winding; 4) Tetrabutylammonium hydroxide solution, L-hydroxyproline and α-cellulose are uniformly mixed to prepare an impregnation solution, the fractal fiber is impregnated in the impregnation solution, and then washed with deionized water, dried and cut to obtain a composite fiber material; 5) Take 900-950 parts of aggregate, 60-70 parts of fly ash, and 4-5.5 parts of composite fiber material and mix them in a dry manner. Then add 60-70 parts of asphalt and continue mixing. Then add 30-50 parts of mineral powder and mix evenly.

[0009] Preferably, in step 1), the mass percentage of polyacrylonitrile in the precursor solution A is 15-18.5%; And / or, in step 1), the mass percentage of the metal oxide in the precursor solution A is 0.15-0.3%; And / or, in step 1), the solvent is one of N,N-dimethylformamide, dimethyl sulfoxide, sulfolane, and dimethylacetamide.

[0010] Preferably, the method for preparing the metal oxide comprises the following steps: S1: Mix polysaccharide, urea, attapulgite and deionized water evenly, then add ferric chloride and manganese chloride, control the pH value to 3-3.5, and stand for ultrasonic dispersion to obtain a slurry; S2: Slowly add the slurry dropwise into a sodium hydroxide solution, age for 2-3 hours, filter out and transfer to an ice bath for cooling, centrifuge, wash with deionized water, dry and grind to obtain the product.

[0011] Preferably, the polysaccharide is one or more of carrageenan, sodium alginate, chitosan and guar gum.

[0012] Preferably, the average particle size of the attapulgite is 20-150 μm.

[0013] Preferably, the molar ratio of Fe:Mn in the slurry is (2-2.5):1.

[0014] Preferably, in step 2), the mass percentage of cyclodextrin in the precursor solution B is 15-18.5%; And / or, in step 2), the mass ratio of calcium chloride, polylauryl methacrylate, polycaprolactone and surfactant is (0.5-0.75):(1-1.5):(2-3):(0.01-0.03); And / or, in the step 2), the surfactant is one of dodecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride and octadecyltrimethylammonium chloride.

[0015] Preferably, in step 3), the flow rate ratio of precursor solution A to precursor solution B is 1:(0.35-0.5).

[0016] Preferably, in step 4), the average length of the composite fiber material is 6 mm; And / or, in step 4), the mass ratio of tetrabutylammonium hydroxide solution, L-hydroxyproline and α-cellulose is 1:(0.05-0.1):(0.1-0.15); And / or, in step 4), the immersion time is 5-10 minutes.

[0017] In a second aspect, the present application provides a high-performance dry powder asphalt mixture, which is prepared using the above-mentioned preparation method.

[0018] In summary, this application has the following beneficial effects: 1. The present application firstly dry mixes aggregate, fly ash and composite fiber material, then adds asphalt for mixing, and finally adds mineral powder. On the one hand, it can reduce the entanglement and agglomeration between fibers, making the composite fiber material more evenly dispersed. On the other hand, it can enhance the bonding force between the components of the mixture, increase the internal friction, and greatly improve the high temperature stability and low temperature crack resistance of the mixture. 2. The fractal fibers made by two-component electrospinning are used in the present application. After being impregnated, they are cut into composite fiber materials of suitable sizes. Compared with traditional basalt fibers, polyester fibers or cellulose fibers, the composite fiber materials of the present application have better interfacial bonding with the mixture matrix. In addition, the composite fiber materials overlap each other to form a bridge fiber network, which makes the asphalt mixture have higher strength and stiffness. In addition, a fractal structure is formed on the fiber surface of the composite fiber material, which has a large specific surface area and can absorb more asphalt. Therefore, the asphalt addition amount in the asphalt mixture of the present application is slightly higher, which also makes the bonding force between the fiber and the mixture stronger, and the dynamic stability of the system is increased, which improves the high temperature stability and anti-cracking performance to a certain extent; 3. In the fractal fiber preparation process of the present application, a certain amount of metal oxide is added to the precursor liquid A to enhance the toughness of the fractal fiber. Precursor liquid B uses polycaprolactone as a substrate, and adds components such as cyclodextrin and polylauryl methacrylate to enhance the interfacial bonding force of the fractal fiber. In addition, the flow rate ratio of precursor liquid A to precursor liquid B is adjusted to make the fractal structure on the fiber surface more uniform, and after impregnation treatment, the micromechanical state between the fiber and the mixture matrix is ​​improved, the interfacial shear strength is enhanced, and the anti-cracking performance and road performance of the mixture are further enhanced. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a load-displacement test data diagram of the composite fiber materials of Examples 1-3 of the present application and the polyacrylonitrile fiber of the control group.

[0020] Figure 2 This is a SEM image of the composite fiber material of Example 3 of the present application. DETAILED DESCRIPTION

[0021] The present application is further described in detail below with reference to the embodiments.

[0022] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0023] This application has undergone a large number of experiments and screenings to examine the performance differences between traditional fiber materials and composite fiber materials, and to optimize the preparation method of composite fiber materials. Without making major adjustments to components such as asphalt and aggregates, the application has further improved the anti-cracking performance and road performance of asphalt mixtures.

[0024] The present application provides a method for preparing a high-performance dry powder asphalt mixture, comprising the following steps: 1) Mix polyacrylonitrile, metal oxide and solvent and stir them to obtain a precursor solution A; 2) Dissolve cyclodextrin in anhydrous ethanol to prepare a base solution; then add calcium chloride, polylauryl methacrylate, polycaprolactone, and a surfactant and mix evenly; then introduce excess carbon dioxide, let stand, and degas to obtain a precursor solution B; 3) Precursor solution A and precursor solution B are respectively delivered into syringes, and conjugate electrospinning is performed under the action of a high voltage electric field, and fractal fibers are obtained after winding; 4) Tetrabutylammonium hydroxide solution, L-hydroxyproline and α-cellulose are uniformly mixed to prepare an impregnation solution, the fractal fiber is impregnated in the impregnation solution, and then washed with deionized water, dried and cut to obtain a composite fiber material; 5) Take 900-950 parts of aggregate, 60-70 parts of fly ash, and 4-5.5 parts of composite fiber material and mix them in a dry manner. Then add 60-70 parts of asphalt and continue mixing. Then add 30-50 parts of mineral powder and mix evenly.

[0025] Preferably, the aggregate includes coarse aggregate and fine aggregate, the coarse aggregate is basalt, and the fine aggregate is limestone. The specific gradation composition of the aggregate is shown in Table 1.

[0026] Table 1 Aggregate gradation composition of this application

[0027] Preferably, the mineral powder of the present application is limestone mineral powder, with a water content of 0.4% and a relative density of 2.705 g / cm -3 .

[0028] Preferably, the composition of the fly ash of the present application is as shown in Table 2.

[0029] Table 2 Composition of fly ash in this application

[0030] Preferably, the asphalt of the present application is SBS modified asphalt, with a needle penetration (0.1 mm) of 72 at 25°C, a PI of 0.5, and a softening point of 86°C.

[0031] Preferably, in step 1), the mass percentage of polyacrylonitrile in the precursor solution A is 15-18.5%; And / or, in step 1), the mass percentage of the metal oxide in the precursor solution A is 0.15-0.3%; And / or, in step 1), the solvent is one of N,N-dimethylformamide, dimethyl sulfoxide, sulfolane, and dimethylacetamide.

[0032] In some specific embodiments, in the step 1), the mass percentage of polyacrylonitrile in the precursor solution A can be 15-15.5%, 15.5-16%, 16-16.5%, 16.5-17%, 17-17.5%, 17.5-18%, or 18-18.5%; more preferably, the mass percentage of polyacrylonitrile in the precursor solution A can be 15%, 15.5%, 16%, 16.2%, 16.5%, 16.8%, 17%, 17.5%, 18%, or 18.5%, and under normal circumstances, better experimental results can be obtained when the mass percentage of polyacrylonitrile in the precursor solution A is 16.5%.

[0033] In some specific embodiments, in the step 1), the mass percentage of metal oxide in the precursor solution A can be 0.15-0.17%, 0.17-0.2%, 0.2-0.23%, 0.23-0.25%, or 0.25-0.3%. More preferably, the mass percentage of metal oxide in the precursor solution A can be 0.15%, 0.17%, 0.19%, 0.2%, 0.23%, 0.25%, 0.28%, or 0.3%. Under normal circumstances, when the mass percentage of metal oxide in the precursor solution A is 0.2%, better experimental results can be obtained.

[0034] Preferably, the method for preparing the metal oxide comprises the following steps: S1: Mix polysaccharide, urea, attapulgite and deionized water evenly, then add ferric chloride and manganese chloride, control the pH value to 3-3.5, and stand for ultrasonic dispersion to obtain a slurry; S2: Slowly add the slurry dropwise into a sodium hydroxide solution, age for 2-3 hours, filter out and transfer to an ice bath for cooling, centrifuge, wash with deionized water, dry and grind to obtain the product.

[0035] Preferably, the polysaccharide is one or more of carrageenan, sodium alginate, chitosan, and guar gum. More preferably, the polysaccharide is composed of carrageenan and sodium alginate in a mass ratio of 1:2.5.

[0036] Preferably, the average particle size of the attapulgite is 20-150 μm. More preferably, when the average particle size of the attapulgite is 50-100 μm, better experimental results can be obtained.

[0037] Preferably, the molar ratio of Fe:Mn in the slurry is (2-2.5): 1. Generally, when the molar ratio of Fe:Mn in the slurry is 2:1, the experimental effect is better.

[0038] Preferably, in step 2), the mass percentage of cyclodextrin in the precursor solution B is 15-18.5%; In some specific embodiments, the mass percentage of cyclodextrin in precursor solution B can be 15-15.5%, 15.5-16%, 16-16.5%, 16.5-17%, 17-17.5%, 17.5-18%, or 18-18.5%. More preferably, the mass percentage of cyclodextrin in precursor solution B can be 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, or 18.5%. Under normal circumstances, when the mass percentage of cyclodextrin in precursor solution B is 18%, better experimental results can be obtained.

[0039] And / or, in step 2), the mass ratio of calcium chloride, polylauryl methacrylate, polycaprolactone and surfactant is (0.5-0.75):(1-1.5):(2-3):(0.01-0.03); In some specific embodiments, in step 2), the mass ratio of calcium chloride, polylauryl methacrylate, polycaprolactone, and surfactant can be 0.5:1:2:0.01, 0.6:1:2:0.01, 0.65:1:2:0.01, 0.7:1:2:0.01, 0.75:1:2:0.01, 0.5:1.2:2:0.01, 0.5:1.5:2:0.01, 0.5:1:2.5:0.01, 0.5:1:3:0.01, 0.6:1.2:2:0.01 1. 0.6:1.5:2:0.01, 0.65:1.5:2:0.01, 0.7:1.5:2:0.01, 0.75:1.5:2:0.01, 0.7:1:2:0.02, 0.75:1:2:0.03, 0.75:1:2.5:0.01, 0.75:1:3:0.01; More preferably, under normal circumstances, when the mass ratio of calcium chloride, polylauryl methacrylate, polycaprolactone and surfactant is 0.6:1.5:3:0.015, the experimental effect is better.

[0040] And / or, in the step 2), the surfactant is one of dodecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride and octadecyltrimethylammonium chloride.

[0041] Preferably, in step 3), the flow rate ratio of precursor solution A to precursor solution B is 1:(0.35-0.5).

[0042] In some specific embodiments, the flow rate ratio of precursor liquid A to precursor liquid B can be 1:(0.35-0.38), 1:(0.38-0.4), 1:(0.4-0.45), 1:(0.45-0.5), and more preferably, the flow rate ratio of precursor liquid A to precursor liquid B can be 1:0.35, 1:0.38, 1:0.4, 1:0.43, 1:0.45, 1:0.5, and, after screening, under normal circumstances, a better experimental effect can be obtained when the flow rate ratio of precursor liquid A to precursor liquid B is 1:0.38.

[0043] Preferably, in step 4), the average length of the composite fiber material is 6 mm; And / or, in step 4), the mass ratio of tetrabutylammonium hydroxide solution, L-hydroxyproline and α-cellulose is 1:(0.05-0.1):(0.1-0.15); In some specific embodiments, the mass ratio of tetrabutylammonium hydroxide solution, L-hydroxyproline and α-cellulose can be 1:0.05:0.1, 1:0.06:0.1, 1:0.07:0.1, 1:0.08:0.1, 1:0.09:0.1, 1:0.05:0.12, 1:0.05:0.15, 1:0.06:0.12, 1:0.06:0.15, 1:0.07:0.12, 1:0.07:0.15, 1:0.08:0.12, 1:0.08:0.15, 1:0.09:0.12, 1:0.09:0.15. Under normal circumstances, when the mass ratio of tetrabutylammonium hydroxide solution, L-hydroxyproline and α-cellulose is 1:0.075:0.15, better experimental results can be obtained.

[0044] And / or, in step 4), the immersion time is 5-10 minutes. Example 1

[0045] The method for preparing the high-performance dry powder asphalt mixture of this embodiment comprises the following steps: 1) Dry the polyacrylonitrile powder (relative molecular weight 5×10 4 ) is dissolved in N,N-dimethylformamide solvent, heated to fully dissolve, and then the metal oxide is added and stirred, and the precursor solution A is obtained by mixing evenly, and the mass fraction of polyacrylonitrile in the precursor solution A is controlled to be 16.5%, and the mass fraction of the metal oxide in the precursor solution A is 0.2%; The preparation method of the metal oxide comprises the following steps: S1: 35 g of polysaccharide, 5 g of urea, 20 g of attapulgite, and 150 mL of deionized water were mixed evenly, and then 2 g of ferric chloride hexahydrate and 0.732 g of manganese chloride tetrahydrate were added, and the pH value was controlled to be 3-3.5. After ultrasonic dispersion, the mixture was allowed to stand to obtain a slurry, and the molar ratio of Fe:Mn in the slurry was 2:1; S2: Slowly add the slurry dropwise into 100 mL of 3M sodium hydroxide solution, age for 3 h, filter out and transfer to an ice bath for cooling, centrifuge, wash three times with deionized water, dry and grind to obtain; 2) β-cyclodextrin was dissolved in anhydrous ethanol to prepare a base solution; then calcium chloride, polylauryl methacrylate, polycaprolactone and a surfactant were added and mixed evenly, and the mass ratio of calcium chloride, polylauryl methacrylate, polycaprolactone and the surfactant was controlled to be 0.6:1.5:3:0.015, and then excessive carbon dioxide was introduced, and the precursor solution B was prepared after standing and degassing, and the mass percentage of cyclodextrin in the precursor solution B was controlled to be 18%; 3) Precursor A and precursor B are delivered to syringe 1 and syringe 2 respectively, and the flow rates of syringe 1 and syringe 2 are controlled so that the flow rate ratio of precursor A and precursor B is 1:0.38. Syringe 1 is negatively charged and syringe 2 is positively charged. Under the action of high-voltage electric field, precursor A and precursor B are stretched into fibers. Under the action of electrostatics, they gather together and form a cone surface. Fibers are formed by drawing and twisting. Fractal fibers are obtained after winding and collection. The voltage of syringe 1 is 18 kV, and the voltage of syringe 2 is 15 kV. The total flow rate of precursor A and precursor B is 3.5 mL / min, and the winding speed is 0.16 mm / s. 4) A 40% by mass tetrabutylammonium hydroxide solution, L-hydroxyproline and α-cellulose were mixed uniformly in a mass ratio of 1:0.075:0.15 to prepare an impregnation solution, and the fractal fiber was immersed in the impregnation solution for 10 minutes, and then washed with deionized water, dried and cut to obtain a composite fiber material with an average length of 6 mm and a diameter of 15 μm; 5) Take 9kg aggregate, 0.6kg fly ash and 0.04kg composite fiber material and put them into an automatic mixer for dry mixing for 90s. Then add 0.6kg molten asphalt and mix thoroughly for 90s. Then add 0.5kg mineral powder and continue mixing for 90s to obtain a high-performance dry powder asphalt mixture.

[0046] The polysaccharide is composed of carrageenan and sodium alginate in a mass ratio of 1:2.5. The average particle size of the attapulgite is 50 μm. Example 2

[0047] The method for preparing the high-performance dry powder asphalt mixture of this embodiment comprises the following steps: 1) Dry the polyacrylonitrile powder (relative molecular weight 5×10 4 ) is dissolved in N,N-dimethylformamide solvent, heated to fully dissolve, and then the metal oxide is added and stirred, and the precursor solution A is obtained by mixing evenly, and the mass fraction of polyacrylonitrile in the precursor solution A is controlled to be 16.5%, and the mass fraction of the metal oxide in the precursor solution A is 0.2%; The preparation method of the metal oxide comprises the following steps: S1: 35 g of polysaccharide, 5 g of urea, 20 g of attapulgite, and 150 mL of deionized water were mixed evenly, and then 2 g of ferric chloride hexahydrate and 0.732 g of manganese chloride tetrahydrate were added, and the pH value was controlled to be 3-3.5. After ultrasonic dispersion, the mixture was allowed to stand to obtain a slurry, and the molar ratio of Fe:Mn in the slurry was 2:1; S2: Slowly add the slurry dropwise into 100 mL of 3M sodium hydroxide solution, age for 3 h, filter out and transfer to an ice bath for cooling, centrifuge, wash three times with deionized water, dry and grind to obtain; 2) β-cyclodextrin was dissolved in anhydrous ethanol to prepare a base solution; then calcium chloride, polylauryl methacrylate, polycaprolactone and a surfactant were added and mixed evenly, and the mass ratio of calcium chloride, polylauryl methacrylate, polycaprolactone and the surfactant was controlled to be 0.6:1.5:3:0.015, and then excessive carbon dioxide was introduced, and the precursor solution B was prepared after standing and degassing, and the mass percentage of cyclodextrin in the precursor solution B was controlled to be 18%; 3) Precursor A and precursor B are delivered to syringe 1 and syringe 2 respectively, and the flow rates of syringe 1 and syringe 2 are controlled so that the flow rate ratio of precursor A and precursor B is 1:0.38. Syringe 1 is negatively charged and syringe 2 is positively charged. Under the action of high-voltage electric field, precursor A and precursor B are stretched into fibers. Under the action of electrostatics, they gather together and form a cone surface. Fibers are formed by drawing and twisting. Fractal fibers are obtained after winding and collection. The voltage of syringe 1 is 18 kV, and the voltage of syringe 2 is 15 kV. The total flow rate of precursor A and precursor B is 3.5 mL / min, and the winding speed is 0.16 mm / s. 4) A 40% by mass tetrabutylammonium hydroxide solution, L-hydroxyproline and α-cellulose were mixed uniformly in a mass ratio of 1:0.075:0.15 to prepare an impregnation solution, and the fractal fiber was immersed in the impregnation solution for 10 minutes, and then washed with deionized water, dried and cut to obtain a composite fiber material with an average length of 6 mm and a diameter of 15 μm; 5) Take 9.5kg aggregate, 0.7kg fly ash and 0.055kg composite fiber material and put them into an automatic mixer for dry mixing for 90s. Then add 0.7kg molten asphalt and mix thoroughly for 90s. Then add 0.5kg mineral powder and continue mixing for 90s to obtain a high-performance dry powder asphalt mixture.

[0048] The polysaccharide is composed of carrageenan and sodium alginate in a mass ratio of 1:2.5. The average particle size of attapulgite is 100 μm. Example 3

[0049] The method for preparing the high-performance dry powder asphalt mixture of this embodiment comprises the following steps: 1) Dry the polyacrylonitrile powder (relative molecular weight 5×10 4 ) is dissolved in N,N-dimethylformamide solvent, heated to fully dissolve, and then the metal oxide is added and stirred, and the precursor solution A is obtained by mixing evenly, and the mass fraction of polyacrylonitrile in the precursor solution A is controlled to be 16.5%, and the mass fraction of the metal oxide in the precursor solution A is 0.2%; The preparation method of the metal oxide comprises the following steps: S1: 35 g of polysaccharide, 5 g of urea, 20 g of attapulgite, and 150 mL of deionized water were mixed evenly, and then 2 g of ferric chloride hexahydrate and 0.732 g of manganese chloride tetrahydrate were added, and the pH value was controlled to be 3-3.5. After ultrasonic dispersion, the mixture was allowed to stand to obtain a slurry, and the molar ratio of Fe:Mn in the slurry was 2:1; S2: Slowly add the slurry dropwise into 100 mL of 3M sodium hydroxide solution, age for 3 h, filter out and transfer to an ice bath for cooling, centrifuge, wash three times with deionized water, dry and grind to obtain; 2) β-cyclodextrin was dissolved in anhydrous ethanol to prepare a base solution; then calcium chloride, polylauryl methacrylate, polycaprolactone and a surfactant were added and mixed evenly, and the mass ratio of calcium chloride, polylauryl methacrylate, polycaprolactone and the surfactant was controlled to be 0.6:1.5:3:0.015, and then excessive carbon dioxide was introduced, and the precursor solution B was prepared after standing and degassing, and the mass percentage of cyclodextrin in the precursor solution B was controlled to be 18%; 3) Precursor A and precursor B are delivered to syringe 1 and syringe 2 respectively, and the flow rates of syringe 1 and syringe 2 are controlled so that the flow rate ratio of precursor A and precursor B is 1:0.38. Syringe 1 is negatively charged and syringe 2 is positively charged. Under the action of high-voltage electric field, precursor A and precursor B are stretched into fibers. Under the action of electrostatics, they gather together and form a cone surface. Fibers are formed by drawing and twisting. Fractal fibers are obtained after winding and collection. The voltage of syringe 1 is 18 kV, and the voltage of syringe 2 is 15 kV. The total flow rate of precursor A and precursor B is 3.5 mL / min, and the winding speed is 0.16 mm / s. 4) A 40% by mass tetrabutylammonium hydroxide solution, L-hydroxyproline and α-cellulose were mixed uniformly in a mass ratio of 1:0.075:0.15 to prepare an impregnation solution, and the fractal fiber was immersed in the impregnation solution for 10 minutes, and then washed with deionized water, dried and cut to obtain a composite fiber material with an average length of 6 mm and a diameter of 15 μm; 5) Take 9kg aggregate, 0.65kg fly ash and 0.05kg composite fiber material and put them into an automatic mixer for dry mixing for 90s. Then add 0.65kg molten asphalt and mix thoroughly for 90s. Then add 0.35kg mineral powder and continue mixing for 90s to obtain a high-performance dry powder asphalt mixture.

[0050] The polysaccharide is composed of carrageenan and sodium alginate in a mass ratio of 1:2.5. The average particle size of the attapulgite is 50 μm.

[0051] Control group The preparation method of the high-performance dry powder asphalt mixture of the control group includes the following steps: 9 kg of aggregate, 0.6 kg of fly ash and 0.04 kg of polyacrylonitrile fiber (average length 6 mm, diameter about 15 μm) were put into an automatic mixer for dry mixing for 90 seconds, and then 0.6 kg of molten asphalt was added and mixed thoroughly for 90 seconds. Then 0.5 kg of mineral powder was added and mixed for a further 90 seconds to obtain a high-performance dry powder asphalt mixture.

[0052] Performance testing 1. The high performance dry powder asphalt mixtures of Examples 1-3 and the control group were subjected to a Marshall stability test. The test results are shown in Table 3.

[0053] Table 3 Marshall test results of high performance dry powder asphalt mixtures of Examples 1-3 and the control group

[0054] It can be seen from Table 3 that the composite fiber material of the present application has higher stability and better crack resistance than conventional polyacrylonitrile fiber.

[0055] 2. Take the high-performance dry powder asphalt mixture of Examples 1-3 and the control group, and according to the requirements of the "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011), use a wheel roller to roll the mixture into plate-shaped specimens. After the plate specimens are cooled at room temperature for 12 hours, use a fully automatic cutting machine to process them into prismatic specimens with a length of 250 mm, a width of 30 mm, and a height of 35 mm. Three specimens are prepared for each group of mixtures.

[0056] The prepared specimens were placed in a -10°C constant temperature water tank and kept warm until the temperature of the specimens was consistent with the temperature of the constant temperature water tank box and the temperature reading was stable; after the insulation was completed, a multifunctional fully automatic asphalt pressure tester was used to load the span of the prism at a loading rate of 50 mm / min. The parameters of the specimens after loading were recorded, and the mid-span height and width were measured respectively. The anti-cracking properties such as bending tensile strain and bending stiffness modulus were calculated according to the requirements of the specification. The specific results are shown in Table 4.

[0057] Table 4 Test results of crack resistance of high performance dry powder asphalt mixture of Examples 1-3 and the control group

[0058] 3. The above-mentioned asphalt and mineral powder were mixed evenly at a powder-to-binder ratio of 1:1 as the matrix material. The uncut composite fiber materials of Examples 1-3 and the polyacrylonitrile fiber of the control group were taken, the fibers were straightened, one end was buried in the matrix material, and then a tensile load was applied along the axial direction of the fibers to gradually pull out the fibers. The tensile load-displacement relationship was recorded using a micromechanical experimental platform. The test parameters were: fiber length 15 cm, tensile speed 3 mm / min, temperature 25 ° C, and burial depth 6 mm. The test results are as follows: Figure 1 As shown, it can be seen that the fractal fiber of the present application has higher peak load and stability than traditional polyacrylonitrile fiber, which helps to improve the anti-cracking performance and road performance of the mixture.

[0059] The composite fiber material of Example 3 was tested by scanning electron microscope. The test results are as follows: Figure 2 As shown, it can be seen that the surface of the composite fiber material of the present application has a fractal structure, which is beneficial to improving the anti-cracking performance of the mixture.

[0060] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a high-performance dry powder asphalt mixture, characterized in that: The steps include: 1) Mix polyacrylonitrile, metal oxide and solvent and stir them to obtain precursor solution A; 2) Dissolve cyclodextrin in anhydrous ethanol to prepare a base solution; then add calcium chloride, polylauryl methacrylate, polycaprolactone, and a surfactant and mix evenly; then introduce excess carbon dioxide, let stand, and degas to obtain a precursor solution B; 3) Precursor solution A and precursor solution B are respectively delivered into syringes, and conjugate electrospinning is performed under the action of a high voltage electric field, and fractal fibers are obtained after winding; 4) Tetrabutylammonium hydroxide solution, L-hydroxyproline and α-cellulose are uniformly mixed to prepare an impregnation solution, the fractal fiber is impregnated in the impregnation solution, and then washed with deionized water, dried and cut to obtain a composite fiber material; 5) Take 900-950 parts of aggregate, 60-70 parts of fly ash, and 4-5.5 parts of composite fiber material and mix them in a dry manner. Then add 50-60 parts of asphalt and continue mixing. Then add 30-50 parts of mineral powder and mix evenly.

2. The method for preparing a high-performance dry powder asphalt mixture according to claim 1, characterized in that: In the step 1), the mass percentage of polyacrylonitrile in the precursor solution A is 15-18.5%; And / or, in step 1), the mass percentage of the metal oxide in the precursor solution A is 0.15-0.3%; And / or, in step 1), the solvent is one of N,N-dimethylformamide, dimethyl sulfoxide, sulfolane, and dimethylacetamide.

3. The method for preparing a high-performance dry powder asphalt mixture according to claim 2, characterized in that: The preparation method of the metal oxide comprises the following steps: S1: Mix polysaccharide, urea, attapulgite and deionized water evenly, then add ferric chloride and manganese chloride, control the pH value to 3-3.5, and stand for ultrasonic dispersion to obtain a slurry; S2: Slowly add the slurry dropwise into a sodium hydroxide solution, age for 2-3 hours, filter out and transfer to an ice bath for cooling, centrifuge, wash with deionized water, dry and grind to obtain the product.

4. The method for preparing a high-performance dry powder asphalt mixture according to claim 3, characterized in that: The polysaccharide is one or more of carrageenan, sodium alginate, chitosan and guar gum.

5. The method for preparing a high-performance dry powder asphalt mixture according to claim 3, characterized in that: The average particle size of the attapulgite is 20-150 μm.

6. The method for preparing a high-performance dry powder asphalt mixture according to claim 3, characterized in that: The molar ratio of Fe:Mn in the slurry is (2-2.5):

1.

7. The method for preparing a high-performance dry powder asphalt mixture according to claim 1, characterized in that: In the step 2), the mass percentage of cyclodextrin in the precursor solution B is 15-18.5%; And / or, in step 2), the mass ratio of calcium chloride, polylauryl methacrylate, polycaprolactone and surfactant is (0.5-0.75):(1-1.5):(2-3):(0.01-0.03); And / or, in the step 2), the surfactant is one of dodecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride and octadecyltrimethylammonium chloride.

8. The method for preparing a high-performance dry powder asphalt mixture according to claim 1, characterized in that: In the step 3), the flow rate ratio of the precursor solution A to the precursor solution B is 1:(0.35-0.5).

9. The method for preparing a high-performance dry powder asphalt mixture according to claim 1, characterized in that: In the step 4), the average length of the composite fiber material is 6 mm; And / or, in step 4), the mass ratio of tetrabutylammonium hydroxide solution, L-hydroxyproline and α-cellulose is 1:(0.05-0.1):(0.1-0.15); And / or, in step 4), the immersion time is 5-10 minutes.

10. A high-performance dry powder asphalt mixture, prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Composite fiber material used in mixed asphalt material

    CN103739239A

  • Preparation method of fiber and cold patch asphalt mixture

    CN106431088A

  • Antistatic acrylic fiber and preparation method thereof

    CN105155015A

  • Asphalt mixture and preparation method thereof

    CN116177927A

  • Composite waterproof anti-crack noise-reduction ultrathin wearing layer asphalt mixture and preparation method thereof

    CN116514456A